Communication techniques for improved acceptance and adherence with therapeutic footwear. (April 2017) - van Netten, Jaap J; Francis, Anthony; Morphet, Ashley; Fortington, Lauren V; Postema, Klaas; Williams, Anita
Background and aim: Clients' acceptance and adherence with orthoses can be influenced by a clinician's communication skills. In this clinical note, we describe two communication techniques, in the context of therapeutic footwear. Technique: Person-centred communication involves engaging with and listening to the attitudes of the client towards their condition, as well as discussing acceptance and expectations, in a structured consultation. Building a relationship is crucial and requires clients to feel heard and understood. An important influence on the acceptance and adherence is that a client makes a conscious decision to receive their device. This active receipt can be facilitated through shared decision making, wherein clinicians give clear, relevant and meaningful examples, based on clinical evidence, and ensure this is understood. Discussion: Two communication techniques for clinicians providing therapeutic footwear are described. These can be adapted for use with provision of other assistive technologies to improve client acceptance and adherence. Clinical relevance: Small changes in how clinicians communicate to their clients in daily practice can have a big influence on the subsequent acceptance and adherence with therapeutic footwear and indeed other prescribed assistive technologies.